National Quality Measures for Child Mental Health Care: Background, Progress, and Next Steps - Zima, Bonnie T. (American Academy of Pediatrics, 2013)
OBJECTIVE: To review recent health policies related to measuring child health care quality, the selection processes of national child health quality measures, the nationally recommended quality measures for child mental health care and their evidence strength, the progress made toward developing new measures, and early lessons learned from these national efforts. METHODS: Methods used included description of the selection process of child health care quality measures from 2 independent national initiatives, the recommended quality measures for child mental health care, and the strength of scientific evidence supporting them. RESULTS: Of the child health quality measures recommended or endorsed during these national initiatives, only 9 unique measures were related to child mental health. CONCLUSIONS: The development of new child mental health quality measures poses methodologic challenges that will require a paradigm shift to align research with its accelerated pace.